Conceptual and methodological aspects of relations between discrimination and health in epidemiological studies Aspectos conceituais e metodológicos das relações entre discriminação e saúde em estudos epidemiológicos - João Luiz Bastos; Eduardo Faerstein (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
This article addresses conceptual and methodological aspects of the relations between discrimination and health from an epidemiological perspective. Definitions of discrimination and related constructs are reviewed, and the main theories underlying their association with health are presented. Scales developed to assess discrimination are discussed, in conjunction with a new instrument, devised to operationalize the concept in Brazilian epidemiological surveys. As a relatively unpredictable and uncontrollable source of psychosocial stress, discrimination has been consistently associated with adverse health outcomes and behaviors, particularly mental disorders, smoking, and alcohol use. However, progress in the area depends partly on dealing with aspects related to the assessment of the phenomenon, such as the definition of a construct map and simultaneous measurement of different types of discrimination. Research involving these aspects will enhance our understanding of discrimination and its health consequences, thus increasing our ability to reduce its social occurrence. Abordam-se aspectos conceituais e metodológicos das relações entre discriminação e saúde, sob uma perspectiva epidemiológica. São revisadas definições de discriminação, construtos correlatos e apresentadas as teorias subjacentes à interpretação de suas associações com saúde. Discutem-se os instrumentos desenvolvidos para aferição da discriminação e uma proposta para sua operacionalização em inquéritos epidemiológicos brasileiros. Enquanto fonte de estresse psicossocial relativamente imprevisível e de difícil controle, a discriminação tem sido consistentemente associada com piores condições/comportamentos em saúde, sobretudo transtornos mentais, tabagismo e uso de álcool. Entretanto, avanços na área dependem, em parte, do enfrentamento de questões vinculadas à aferição do fenômeno, como a definição de um mapa do construto e a necessidade de avaliar diferentes discriminações simultaneamente. A exploração desses aspectos propiciará uma compreensão mais ampla da discriminação e de suas consequências sobre a saúde, aumentando nossa capacidade de reduzir sua ocorrência na sociedade.